OXIDIZED ECLOGITES AND GARNET-BLUESCHISTS FROM OMAN: P-T PATH MODELLING IN THE NCFMASHO SYSTEM - Warren C.J.; Waters D.J. (My University, 2006)
Eclogites and garnet-blueschists exposed at the deepest structural levels of the Oman Mountains in north-eastern Saih Hatat, Oman, indicate that the Arabian continental margin was subducted and subsequently exhumed. The peak metamorphic pressure has been a matter of debate for over a decade, with initial thermobarometric estimates, based on garnet-clinopyroxene-phengite barometry and the presence of radial cracks around quartz inclusions in garnet, yielding values in excess of 20 kbar; these estimates have been questioned by some researchers. The high-pressure minerals (glaucophane, omphacite and epidote) contain significant amounts of ferric iron, previously postulated to displace the stability fields of the eclogite and blueschist assemblages to less extreme conditions. In the present study, we have calculated phase diagrams and pseudosections in the model system NCFMASHO, using the program thermocalc and the thermodynamic database of Holland and Powell, which incorporates data for Fe3+-bearing end-members. It is found that the phase compositions and modal abundances for typical bulk compositions are matched successfully at 520 ± 15 °C and 20 ± 1.6 kbar for the eclogites and 510-530 °C and 17-20 kbar for the garnet blueschists. These results support the original high-pressure estimates for the eclogites, and indicate that crossitic amphibole and aegirine-rich pyroxene do not necessarily reflect lower pressure conditions. The data set and activity models are applicable to other oxidized high (and ultra-high) pressure mineral assemblages. © 2006 Blackwell Publishing Ltd.
Keywords: ECLOGITE; OMAN; P-T PATHS; SUBDUCTION; THERMO-CALC